2020
DOI: 10.1016/j.brainres.2019.04.017
|View full text |Cite
|
Sign up to set email alerts
|

The orexin-1 receptor antagonist SB-334867 reduces motivation, but not inhibitory control, in a rat stop signal task

Abstract: There is considerable clinical interest in the neuropeptide orexin/hypocretin for its ability to regulate motivation and reward as well as arousal and wakefulness. For instance, antagonists for the orexin-1 receptor (OxR1) are thought to hold great promise for treating drug addiction and disorders associated with overeating, as these compounds repeatedly have been found to suppress seeking of various drugs of abuse as well as highly palatable foods in preclinical models. Given the hypothesized role of OxR1 sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 87 publications
(140 reference statements)
2
10
0
Order By: Relevance
“…fentanyl, nor any effect on lever pressing for sucrose in fentanyl experienced rats 9 . This is consistent with previous studies demonstrating no effect of systemic SB on general locomotor activity in either an open field apparatus 5,12 or a cognitive task requiring motor engagement 50 . Moreover, here we found that SB treatment had no effect on inactive lever responding during cued reinstatement tests across all treatment groups, further supporting a selective effect of SB on motivated, drug-seeking behaviors.…”
Section: Role Of Ox1r Signaling In Inta-induced Addiction Behaviorssupporting
confidence: 93%
“…fentanyl, nor any effect on lever pressing for sucrose in fentanyl experienced rats 9 . This is consistent with previous studies demonstrating no effect of systemic SB on general locomotor activity in either an open field apparatus 5,12 or a cognitive task requiring motor engagement 50 . Moreover, here we found that SB treatment had no effect on inactive lever responding during cued reinstatement tests across all treatment groups, further supporting a selective effect of SB on motivated, drug-seeking behaviors.…”
Section: Role Of Ox1r Signaling In Inta-induced Addiction Behaviorssupporting
confidence: 93%
“…fentanyl, nor any effect on lever pressing for sucrose in fentanyl experienced rats 9 . This is consistent with previous studies demonstrating no effect of systemic SB on general locomotor activity in either an open field apparatus 5,12 or a cognitive task requiring motor engagement 50 . Moreover, here we found that SB treatment had no effect on inactive lever responding during cued reinstatement tests across all treatment groups, further supporting a selective effect of SB on motivated, drug-seeking behaviors.…”
Section: Role Of Ox1r Signaling In Inta-induced Addiction Behaviorssupporting
confidence: 93%
“…in a counterbalanced fashion 30 minutes prior to BE testing. This dose of SB was selected based on previous studies indicating that this dose reliably affects motivated reward seeking, including for food ( Fragale et al, 2019 ; James et al, 2019a , 2019b ; Barson, 2020 ; Mohammadkhani et al, 2020 ; Wiskerke et al, 2020 ). The drug and vehicle were prepared as described previously ( Smith et al, 2009 ).…”
Section: Methodsmentioning
confidence: 99%